Comparison of Outcomes for Normal Saline and an Antiseptic Solution for Negative-Pressure Wound Therapy with Instillation. Issue 5 (November 2015) - Kim, Paul J.; Attinger, Christopher E.; Oliver, Noah; Garwood, Caitlin; Evans, Karen K.; Steinberg, John S.; Lavery, Larry A.
Abstract : Background: Negative-pressure wound therapy with instillation is an adjunctive treatment that uses periodic instillation of a solution and negative pressure for a wide diversity of wounds. A variety of solutions have been reported, with topical antiseptics as the most frequently chosen option. The objective of this study was to compare the outcomes of normal saline versus an antiseptic solution for negative-pressure wound therapy with instillation for the adjunctive treatment of infected wounds. Methods: This was a prospective, randomized, effectiveness study comparing 0.9% normal saline versus 0.1% polyhexanide plus 0.1% betaine for the adjunctive treatment of infected wounds that required hospital admission and operative débridement. One hundred twenty-three patients were eligible, with 100 patients randomized for the intention-to-treat analysis and 83 patients for the per-protocol analysis. The surrogate outcomes measured were number of operative visits, length of hospital stay, time to final surgical procedure, proportion of closed or covered wounds, and proportion of wounds that remained closed or covered at the 30-day follow-up. Results: There were no statistically significant differences in the demographic profiles in the two cohorts except for a larger proportion of male patients ( p = 0.004). There was no statistically significant difference in the surrogate outcomes with the exception of the time to final surgical procedure favoring normal saline ( p = 0.038). Conclusion: The authors' results suggest that 0.9% normal saline may be as effective as an antiseptic (0.1% polyhexanide plus 0.1% betaine) for negative-pressure wound therapy with instillation for the adjunctive inpatient management of infected wounds. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, II.